A Comparison of Intravascular Imaging Modalities for Detection of Stent Struts in Acute Coronary Syndrome. (February 2016) - Hyeon, Seong Hyeop; Lee, Wang Soo; Kim, Doo Il; Shin, Eun Seok; Kim, Ki Seok; Hong, Young Joon; Lee, Sung Yun; Won, Hoyoun; Kim, Tae Ho; Kim, Sang‐Wook
Abstract : Background: We used optical coherence tomography (OCT) and intravascular ultrasound (IVUS) to assess the struts of implanted stents in patients with acute coronary syndrome (ACS). Methods: A totle of 10, 756 stent struts were analyzed with OCT in 42 patients of ACS. Of them, both of IVUS and OCT imaging were performed in 33 patients. Appearance of stent struts was classified as well apposed, buried, malapposed, and nondetectable, and the number of stent struts were counted by OCT and IVUS was compared. Results: Most of stent struts were well apposed (78.1%, 8, 407/10, 756). However, malapposed struts were 5.6% (607/10, 756), and 14.1% (1, 514/10, 756) of stent struts were buried by thrombus. The nondetectable struts were 2.11% (228/10, 756) in ACS. 94.7% (216/228) of nondetectable stent struts were associated with red thrombus, and plaque prolapse was in 5.3% (12/228). The number of stent struts counted by OCT were larger than that of IVUS. The mean number of stent struts at the proximal and distal stent edges were 24 ± 6.57 in OCT, the stent struts IVUS counted were 20 ± 4.18 (P < 0.0001). Although the frequency of malapposed struts were similar 4.6% (376/8, 248) in OCT versus 4.8% (369/7, 674) in IVUS (P = 0.788). Stent struts were often buried by thrombus in ACS 15.2% (1, 252/8, 248) in OCT versus 9.7% (747/7, 674) in IVUS; P = 0.006. The nondetectable struts were fewer in IVUS than OCT 0.2% (16/7, 674) in IVUS versus 2.2% (187/8, 248) in OCT; P < 0.0001. Conclusion: Stent struts are frequently buried and nondetectable due to thrombi burden in ACS patients. Adequate thrombus removal and proper selection of the imaging device is warranted in ACS. (J Interven Cardiol 2016;29:99–107)